Análise morfoagronômica e química de progênies C2 de Lippia alba e atividade formicida dos óleos essenciais contra Acromyrmex balzani - Jesus, William Santos de (2022)
Lippia alba is a popular Brazilian herb known as lemon balm. It has several chemotypes in nature, which makes for different chemical patterns that are widely used by industries of various segments and in traditional medicine. The objective of the present study was to evaluate the morphoagronomic and chemical performance of Lippia alba progenies from the second recurrent selection cycle in different harvest seasons, and to evaluate the formicidal activity of its essential oils (EOs). The accessions LA56, LA-57, and LA-70 were recombined among progenies selected from the first recurrent selection cycle: LA-56-03, LA-57-10, and LA-70- 01; and five C2 progenies were triple: LA-56-03-01, LA-56-03-02, LA-57-10-02, LA-57-10- 05, and LA-70-01-01. The experiment was monitored at the experimental farm “Campus Rural da UFS”. EOs were obtained by hydrodistillation and later chemically analyzed by gas chromatography to determine their constituents. Morphoagronomic evaluation showed that most genotypes had upright growth habit, with plant height ranging from 45.92 to 94.42 cm, plant width from 94.33 to 397.75 cm, leaf area from 2.38 to 6.51 cm2 , leaf length from 2.76 to 3.82 cm, leaf width from 1.34 to 2.35 cm, internode length from 2.75 to 5.08 cm, dry matter from 3.43 to 30.53 g.plant-1 , EO content from 0.83% to 3.39%, and EO yield from 0.05 to 1.02 mL.plant-1 . In the study on the effect of time of harvest for essential oil content, the overall average of yield in the dry season (2.18%) was higher than that in the rainy season (1.50%). Within the dry season, all C2 progenies attained lower averages than the C1 progenies and their parental accessions. In cluster analysis, two groups were formed in both harvest periods, based on the chemical composition of the initiated oils. Group 1 consisted of 10 of the 11 genotypes evaluated and was characterized by higher mean values of carvone and limonene compounds. Two subgroups were also observed within Group 1. Group 2 was formed by a single C2 progeny (LA-57-10-02) and was characterized by the compounds germacrene D (20.77%), myrcene (15.03%), (E)-caryophyllene (6, 10%), (E)-nerolidol (5.91%), and linalool (5.80%). In general, essential oils taken in the dry season bring about higher mortality (45.13%) in the ants than those obtained in the rainy season (37.01%). The genotypes LA-56-03-01 and LA-57-10-02, whose essential oils had less than 40% carvone, exceeded the mortality rate provided by the compound in isolation.